Adaptation of the technology for mounting on the surface of controllers for the deployment of liquid crystal. - M. A., Antonio Andrés; Suárez Fernández, A.; Nolasco Suarez, C.; Hernández Mateos, E.; Martínez Martínez, F.; Romero Vázquez, J. (Revista Mexicana de Ingenieria Biomedica, 1991)
The method followed is presented to perform, by means of conventional techniques, the assembly of the surface of an LCD controller that is manufactured only in the encapsulation for surface mounting. Initially, the importance of the domain of technology for those who design and contribute to the creation of an access device for devices of the ASIC type is highlighted.